2015
DOI: 10.1039/c5gc00381d
|View full text |Cite
|
Sign up to set email alerts
|

Silica-nanosphere-based organic–inorganic hybrid nanomaterials: synthesis, functionalization and applications in catalysis

Abstract: SHARMA, S.; DUTTA, S.; ZBORIL, R.; GAWANDE, M. B.; Green Chem. 17 (2015) 6, 3207-3230, http://dx.doi.org/10.1039/C5GC00381D ; Dep. Chem., Univ. Delhi, Delhi 110 007, India; Eng.) -S. Adam 32-262

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(127 citation statements)
references
References 184 publications
(174 reference statements)
0
127
0
Order By: Relevance
“…In continuation of our efforts for synthesis of organic compounds using sustainable protocols (Gawande et al, 2013a,b,c,d, 2014a,b,c; Kale et al, 2013; Sharma et al, 2015), in this work, we have successfully developed a mild and ecofriendly synthesis of benzyl phosphonates using PEG/KI as a catalytic system. In this protocol, PEG not only acts as a reaction medium but also as a PTC.…”
Section: Resultsmentioning
confidence: 94%
“…In continuation of our efforts for synthesis of organic compounds using sustainable protocols (Gawande et al, 2013a,b,c,d, 2014a,b,c; Kale et al, 2013; Sharma et al, 2015), in this work, we have successfully developed a mild and ecofriendly synthesis of benzyl phosphonates using PEG/KI as a catalytic system. In this protocol, PEG not only acts as a reaction medium but also as a PTC.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, the use of nanocatalysts has increased rapidly and has resulted in the development of several active and efficient nanocatalysts for various protocols [8][9][10][11][12][13][14][15][16][17][18]. These systems have several advantages over conventional catalysts, such as superior activity and improved stability.…”
Section: Introductionmentioning
confidence: 99%
“…in situ removal of water and moisture absorbing materials are the two options [25][26][27], which were often observed with minimum success and inconsistent yields [25][26][27]. Recent mechanism studies had suggested that moisture was not the real problem and the catalysts offering more surface area have proven to be more useful [28][29][30][31]. The use of Fe 3 O 4 @SiO 2 was first of its sort and near doubling of reaction yield is in expected lines considering our similar observation with thiophenes, terpyridine, quinazoline and isoxazole [23].…”
Section: Synthesis Of 2-amino-5-carboethoxy-4-hydroxypyrimidine Withoutmentioning
confidence: 99%